Brother’s mandate: Antigone for postmodernity (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Of the many possible readings of Sophocles' Antigone, we highlight the nature of the tragic conflict, which has its roots in previous values to the established social order, and which can be considered useful material for re-founding the political status in postmodernity. From the text commentary, we note that Antigone does not attack the social order, but she hopes to consolidate it on an imperturbable basis that embodies the critique of instrumental rationality, inaugurated by sophistry and revived successively in modernity. This affirms existentially the ethics of fraternal love as a humanization of the order of the universe. We propose to extend the notion of consanguineous brother and extend it to the idea of brother as “the other” in the framework of postmodern societies, spaces of multicultural intention, to have a principle of ethical rescue. In this re-reading, the archaic notions of religiosity, funeral honor, and family piety are updated.
Keywords: Sophocles; Antigone; ethics; postmodern society